Two adherent blood cysts in subvalvular apparatus of the mitral valve causing severe left ventricular outflow tract obstruction. Issue 2 (August 2018) - Bagheri, Abdolhamid; Ansariaval, Zahra; Khani, Mohammad; Shekarkhar, Shadi; Baghayi, Ramin; Sharifi, Tahmineh
Abstract: Blood cysts in the heart are often incidentally found during post-mortem examinations in infants, and usually do not cause clinical symptoms. They almost always regress spontaneously, and only a few cases of embolization or valvular dysfunction have been reported previously. We report a 62-year-old man who presented with chest discomfort and dyspnea on exertion for several years, and was found to have a dynamic murmur in left ventricular outflow tract (LVOT) on physical examination. His echocardiogram demonstrated two large blood cysts attached to the subvalvular apparatus of mitral valve, causing significant LVOT obstruction and mild to moderate mitral regurgitation. The cysts were surgically excised and pathology confirmed simple blood cysts. <Learning objective: To the best of our knowledge, this is the first reported case of twin blood cysts with severe left ventricular outflow tract obstruction in an adult, since most of these cysts either regress spontaneously in childhood or remain asymptomatic in adults.>